Solusi Pengurangan Emisi Karbon dari Sektor Keuangan dengan Pendekatan Design Thinking - Muhamad Rifnaldy Pratama; Handi Susila; Melinda Nur Wijayanti; Asep Taryana (Syntax Idea)
Abstracts are made in two languages, English and Bahasa Indonesia. Abstract more Climate change poses a significant threat to the global economy, particularly through increased intensity of natural disasters and disruptions to the financial system. This research aims to develop a design thinking-based solution to reduce carbon emissions from the financial sector in Indonesia. The research method involves an analytical approach with design thinking stages: empathy, problem definition, ideation, prototyping, and testing. The results show that this approach enables the creation of adaptive and data-driven solutions, such as the implementation of green financing that includes credit transition, macroprudential policy, financial product development, and collaboration between stakeholders. These solutions have the potential to support the transition to a low-carbon economy, increase green investment, and create green jobs. In conclusion, design thinking is an effective approach to address climate change impacts through innovation in the financial sector. This study recommends strengthening policy implementation and public education related to green financing.